Հակոբ Ա եպիսկոպոս Սյունեցու գործունեության շուրջ (918-958 թթ.) - Վարդան Ալեքսանյան (ՀՀ ԳԱԱ հրատ.)
Епископ Акоп Сюникский-один из знаменитых духовных предводителей Сюникской епархии X века, названный армянскими историографами "мятежником" и "еретиком". Его усердная и плодотворная деятельность способствовала развитию и усилению Сюникского епископата. Bishop Hakob Syunetsi is one of the famous religious leaders of the Syunik eparchy of the 10th century, named by the Armenian ecclesiastical historiographers "insurgent" and "heretic". His assiduous and fruitful activities promoted developing and strengthening the Syunik episcopate.
Keywords: History; Biography; Auxiliary Sciences of History; Medieval History; B Philosophy; Psychology; Religion; BL Religion; D History